2010
DOI: 10.1016/j.resuscitation.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia is associated with a decrease in urine output in acute stroke patients

Abstract: Aims-It is unclear what effect therapeutic hypothermia may have on renal function, because its effect has so far been primarily evaluated in settings in which there may be possible confounding perturbations in cardiovascular and renal physiology, such deep intra-operative hypothermia, general anesthesia, and post-cardiac arrest. We sought to determine if therapeutic hypothermia affects renal function in awake patients with normal renal function who were enrolled into a clinical trial of hypothermia plus intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
0
12
1
1
Order By: Relevance
“…We observed no increased risk of peripheral bleeding, intracerebral hemorrhage, catheter‐related complications, sepsis, pancreatitis, coagulopathy, or liver dysfunction in ICTuS‐L. We observed transient oliguria in the hypothermia treatment group that reversed completely .…”
Section: Introductionmentioning
confidence: 60%
“…We observed no increased risk of peripheral bleeding, intracerebral hemorrhage, catheter‐related complications, sepsis, pancreatitis, coagulopathy, or liver dysfunction in ICTuS‐L. We observed transient oliguria in the hypothermia treatment group that reversed completely .…”
Section: Introductionmentioning
confidence: 60%
“…Guluma et al (2010) evaluated urine output in conscious stroke patients undergoing TH, but found a 5.1-mL/hour decrease in urine output per 1°C decrease in body temperature that persisted during hypothermia maintenance. There are important differences between the Guluma et al and our study.…”
Section: Discussionmentioning
confidence: 99%
“…δ-opioid agonist (79) Reduced inflammation 40 mg/kg -4.13 ± 0.20 °C NMRI mice (33,84,85) DADLE δ-opioid agonist Toxicity at 10 mg/kg: (33) 6 mg/kg -3.2 ± 0.20 °C (33) Mice (84) ↓ Blood pressure (85) Arrhythmia Neurotensin (90) NT69L Neurotensin analog (92) Reduced apoptosis, reduced inflammation 2 mg/kg -2 -5 °C Wistar rats (90) Anti-shivering thermoregulatory effects (86) no cold intolerance response (113,114) Heliox Unknown (113,114) Maintenance of animal temperature at 37 °C still elicited neuroprotection 70%/30% helium/oxygen Sprague-Dawley rats (114) Improved regulation of mitochondrial respiration (114) Reduced adverse effects of nitrogen, inflammation, coagulant actions (116) Hydrogen (119,122) AMP (122) A1 receptor agonist (119) No neuroprotection (119) Larger infarct volume (119) 4 mmol/kg (~1.39 g/kg) (119) 33.1 ± 0.7 °C (119) Sprague-Dawley rats (122) C57/BI6 mice (122) Reduced infarct volume ↑ Incidences of hemorrhagic transformation (122) 50-100 mg/ kg (122) Reduced mortality seizure, and, mortality ↓ Blood pressure ↓ Heart rate Hyperglycemia…”
Section: Snc-80mentioning
confidence: 99%
“…14,29 Further, physiologically, hypothermia can lead to cardiovascular compromise, 30 immune suppression, 6 platelet dysfunction, 31 coagulopathy, 32 and decreased urine output. 33 All of these factors would need to be taken into account before hypothermia becomes the standard of care in the future.…”
Section: Introductionmentioning
confidence: 99%